MACHINE LEARNING PENGAMAN BRANKAS BERBASIS IoT MENGGUNAKAN METODE ALGORITMA NAIVE BAYES PADA PLATFORM THING SPEAK - Faritcan Parlaungan Siallagan, Timbo; Alghifari, Muhammad (STMIK Subang, 2023)
A safe is a tool used to store items, including money, jewelry, or other assets and securities. It is claimed to be simple but carries a high risk because it makes it easy for the safe to be broken into without the owner's knowledge. A household assistant (ART) with the initials HS stole a safe from inside her employer's house located in Taman Kedoya Permai, Kebon Jeruk, West Jakarta,